“THE HYGIENIC AND THE DIRTY” (HEALTH COMMUNICATION FILM ABOUT HEALTHY LIFESTYLE FOR ASMAT TRIBE) - Kevin Sanly Putera; Mariska Amelia Siburian; Reno Vancasavio; Yackie Yackie (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
Healthy lifestyle is one of the human development objective in Asmat regency in Papua. The researcher conducted ethnography for three months in Agats, the city of Asmat to study the cultural practice through Asmat Tribe daily communication. This study aims to obtain a description of a clean and healthy lifestyle, know the obstacles that occur in the process of delivering health communication and develop films that can provide awareness to implement a clean and healthy lifestyle in the Asmat Tribe. This study uses a qualitative method with an ethnographic approach. The results showed that community awareness was still low, obstacles to the delivery of health communication occur because of education, geography, and culture. Then the results of experience and ethnographic products are developed in a short film about a healthy lifestyle. The film titled